Physical Air Quality in The Pneumonia Toddler Room in The Pakusari Puskesmas Working Area, Jember District - Limbong, Andriani Metasari Br; Ma'rufi, Isa (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Pneumonia is a significant health issue, responsible for 14% of child deaths worldwide. At Pakusari Health Center in Jember Regency, cases of pneumonia have risen from 2021 to 2022, placing it among the top 10 health concerns. Pneumonia in young children is caused by viruses, bacteria, fungi, and foreign bodies, exacerbated by physical and chemical contamination. Children under five, who spend much time in the bedroom, are particularly susceptible to this respiratory disease. This study aims to describe the physical air quality in bedrooms and the characteristics of under-five children with pneumonia. This research employs a descriptive, quantitative approach with a case-series design. A sample size of 10 houses was determined using non-probability and purposive sampling techniques. Primary data were gathered from interviews and air quality measurements conducted by the Indonesian Environmental Health and Disease Control (BBTKLPP) Surabaya, focusing on temperature, humidity, and lighting parameters. Findings indicate that 70% of pneumonia cases occur in children aged 0-24 months, with a majority being female.Additionally, 50% of the children received exclusive breastfeeding, and 20% had a history of measles. Based on Ministry of Health Regulation 1077/2011 standards, the room air quality results showed that 40% of air temperature measurements qualified and 60% unqualified, with lighting and humidity also not meeting requirements. However, PM10 levels were 100% within the acceptable range. This suggests that the physical air quality in the bedrooms of children under five with pneumonia is suboptimal, likely due to poor ventilation and infrequent opening of windows and curtains.